Energetic Graphene‐Based Electrochemical Analytical Devices in Nucleic Acid, Protein and Cancer Diagnostics and Detection. Issue 1 (26th April 2013) - Zhu, Chengzhou; Dong, Shaojun
Abstract In recent years graphene (GN) received widespread attention owing to its extraordinary physical and chemical properties. Lately, considerate efforts have been devoted to explore potential applications of GN in life science, especially in disease‐related diagnostics and detection. Especially, the coupling of electrochemical devices with the GN offers an excellent platform to realize the diagnostics and detection of nucleic acid, protein and cancer cells with high performance. This review focuses on the rising progress on GN‐based nanomaterials as advanced electrochemical sensing devices for the detection of the above‐mentioned targets. Future challenges and perspectives in this rapidly developing field are also discussed.